FCS-MPC Strategy with Region-Based Voltage Vector Selection and Kalman Filtering in Shunt Active Power Filters for Power Quality Enhancement - Hnin Ei Phyu; Wunna Swe (AI Society & STMIK Indonesia, 2026)
Power quality issues caused by nonlinear and unbalanced loads, such as harmonics, reactive power demand, and current imbalance, pose significant challenges in modern distribution networks. Shunt Active Power Filters (SAPFs) provide an effective solution, but their performance depends on advanced control strategies. This study proposes a hybrid approach that integrates Finite Control Set Model Predictive Control (FCS-MPC) with region-based voltage vector selection to achieve fast dynamic response and reduced switching losses. The grid voltage cycle is divided into six regions, with only four candidate vectors evaluated per region, minimizing computational complexity. A Kalman filter further enhances prediction accuracy by mitigating measurement noise and control delays. MATLAB/Simulink implementation on a low-voltage distribution network demonstrates effective harmonic suppression, balanced source currents, and robust performance under sudden load variations. Results confirm IEEE 519 compliance, ensuring practical and reliable power quality improvement in smart grids.